2010
DOI: 10.1007/s10903-010-9407-8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Primary Prevention of Asthma: Foreign-Born Children Have Less Association of SES and Pests with Asthma Diagnosis

Abstract: There are no proven interventions for primary prevention of asthma. As asthma prevalence varies globally, comparing asthma in native and foreign-born children might provide insights. We pooled data from five cross sectional asthma surveys (N = 962). Place of birth was associated with asthma (OR = 3.4, P < 0.001). In children not born in the US, lower socio-economic status had no significant effect on asthma (OR = 0.71, P = 0.53), while for children born in the US, the effect was significant (OR = 2.1, P = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…The differences in socioeconomic status and healthcare access observed between nativity categories are consistent with previous reports (1, 12, 19, 27, 30, 33, 45, 46), as are our findings that US-born children have a higher asthma prevalence (2, 11, 19, 35, 47) and prevalence of developmental disabilities (15) compared to IM children. Also consistent are results from oral health studies that have shown that US-born children are less likely than IM children to have cavities (48) or decayed and filled primary teeth (49).…”
Section: Discussionsupporting
confidence: 93%
“…The differences in socioeconomic status and healthcare access observed between nativity categories are consistent with previous reports (1, 12, 19, 27, 30, 33, 45, 46), as are our findings that US-born children have a higher asthma prevalence (2, 11, 19, 35, 47) and prevalence of developmental disabilities (15) compared to IM children. Also consistent are results from oral health studies that have shown that US-born children are less likely than IM children to have cavities (48) or decayed and filled primary teeth (49).…”
Section: Discussionsupporting
confidence: 93%
“…Being male, postponing health care due to concerns about cost, having allergies, and having a mother with asthma and/or allergies were significant risk factors for wheezing severity, which closely aligns with the literature (Carlson & Stroebel, 2001; Holt et al, 2013; Wright et al, 2006). In terms of situating the pest exposure findings within the extant literature, a an analysis which pooled cross-sectional data from five studies revealed that exposure to any home pests was relatively weakly associated with asthma (Woodin et al, 2011). In comparing our PM 2.5 findings to other El Paso studies, which used different methodological approaches, we found similar associations.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income white children in New York (state) had higher rates of indoor risk factors than did middle class white children, and these risk factors were correlated with elevated overnight epinephrine, norepinephrine, and cortisol, but only in the low-income sample (Evans & Marcynyszyn, 2004). Pooling five survey datasets, researchers found that the odds of exposure to household pests was significantly associated with asthma only for children born in the US, and not for children born outside the US (Woodin, Tin, Moy, Palella, & Brugge, 2011). Those studies examined variation based on social characteristics – specifically, income and nativity.…”
Section: Introductionmentioning
confidence: 99%
“…This was however not seen in our population. Pooled data from 5 cross-sectional asthma surveys has previously revealed that the effect of low socioeconomic status and pests in the household on asthma diagnosis differed for children born in- or outside the US [ 30 ], supporting the existence of either protective, or detrimental factors, or both, acting on these children.…”
Section: Discussionmentioning
confidence: 99%